STAKEHOLDER ANALYSIS: DEVELOPMENT AND EMPOWERMENT STUDENT REGIMENT IN INDONESIA DEFENSE SYSTEM - Ahmadani, Faisal; Munandar, Adis Imam; R.D., Agape Zacharia (International Journal of Research -GRANTHAALAYAH, 2020)
The history of Student Regiment in Indonesia is an integral part of Indonesia history as well. But after Indonesia democracy reform, militaristic identity of Student Regiment and degradation Student Regiment’s role in Indonesia Defense System face dilemmatic discourse especially in development and empowerment. This paper applies qualitative method and stakeholder analysis with comparative approach. Based on Law Np. 23/2019, Student Regiment development and empowerment policies should be reviewed. All the policies and regulations on Student Regiment in the future could be supporting Indonesia Defense System management to gain deterrent as the final goal, and Four Ministers Joint Agreement Letter in 2014 should be replace with updated and strong regulation.